Food security in a food abundant world an individual country perspective - Schmitz, Andrew; Kennedy, P. Lynn; Schmitz, Troy Gordon (Emerald, 2016)
Food insecurity can result from various events. When food is abundant, the entitlement to food is limited by endowments, the ability to trade, and potential transfers from family or the government. This volume utilizes a country and regional perspective to examine food insecurity. We consider the interaction between income and the share of household expenditures on food. The epidemiological risk assessment approach to food security issues is utilized as a function of agricultural and production, food distribution, and health policies. The interdependence of food security and climate change is examined. Overall trends in economic growth and poverty reduction, constraints and bottlenecks in agricultural productivity growth, regional trade agreements, and other influential policies are reviewed and discussed. We also consider food security as related to food consumption patterns and obesity. The role of income diversification as well as the impact of Farmer School Fields on food security are examined. The impact of inheritance and transfer entitlements is examined as we consider the role of remittances as well as 'ganyu' or casual labor in determining food security.
Keywords: Food security.; Food security -- Economic aspects.; Nutrition policy.; elektronické knihy; electronic books